2019
DOI: 10.1021/acs.inorgchem.9b01802
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photochemical Studies on Gallium and Indium Complexes of DTPA-PEG3-ArN3 for Radiolabeling Antibodies

Abstract: Photochemistry is a rich source of inspiration for developing alternative methods to functionalize proteins with drug molecules, fluorophores, and radioactive probes. Here, we report the synthesis and photochemical reactivity of a modified diethylenediamine pentaacetic acid chelate that was derivatized with a light-responsive aryl azide group (DTPA-PEG3-ArN3, compound 1). The corresponding nonradioactive and radioactive nat/68Ga3+ and nat/111In3+ complexes of DTPA-PEG3-ArN3 were synthesized and their physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…We recently demonstrated that metal ion binding chelates functionalised with a photoactivatable ArN 3 group can be used to prepare radiolabelled antibodies by either a two‐step conjugation and radiolabelling process or by a novel one‐pot approach . Simultaneous 89 Zr‐radiolabelling and light‐induced conjugation using a photoactivatable DFO‐ArN 3 derivative produced viable PET radiotracers (Scheme ) .…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that metal ion binding chelates functionalised with a photoactivatable ArN 3 group can be used to prepare radiolabelled antibodies by either a two‐step conjugation and radiolabelling process or by a novel one‐pot approach . Simultaneous 89 Zr‐radiolabelling and light‐induced conjugation using a photoactivatable DFO‐ArN 3 derivative produced viable PET radiotracers (Scheme ) .…”
Section: Methodsmentioning
confidence: 99%
“…[61] Our laboratory recently reported the synthesis, radiolabelling, and bimolecular couplingo fp hotoactivatable chelates bearingt he photoactive aryl azide (ArN 3 )g roup to antibodies for use in immuno-PET and RIT ( Figure 2). [41][42][43][44][45] Remarkably, switching the conjugation chemistry from traditional, thermally mediated reactions [10][11][12][13] to ap hoto-initiated reaction allowed us to produce radiolabelled mAbs in as imultaneous( one-pot) process directly from fully formulated antibodies (including Figure 1. Timelines howing the evolution of different photoactive groups used in PAL.…”
Section: Photoradiosynthesis Of Radiolabelled Antibodiesmentioning
confidence: 99%
“…Eur.J. 2020,26,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] www.chemeurj.org Concept the photochemistry for bimolecular protein modification. [67,68] The conformational flexibility of an extended alkyl chain also means that aliphatic carbenes are more likely to undergo intramolecular reactions than the more conformationally rigid aryl carbenes.T hese competing intra-and intermolecularp rocesses are likely to restrict the use of aliphatic diazirines to systems that pre-associate.…”
Section: Aliphatic Diazirinesmentioning
confidence: 99%
See 2 more Smart Citations